P214 Acute exacerbations of COPD: a review of resuscitation status and associations with prognostic factors in hospital admissions. (2nd December 2011) - Rudran, B; Idris, L; Childs, C; Riccio, F; Loganathan, S; Shaw, T J
Abstract : Introduction: Acute exacerbations of COPD are among the most common reasons for hospital admission in the UK. Exacerbations can lead to respiratory failure requiring ventilatory support, and so decisions regarding "escalation" or "ceilings" of treatment are often made early in admission. Such decisions on intubation are inevitably linked to decisions regarding resuscitation status. Prognostic factors should be used when making these decisions and FEV1 should not be used exclusively. We reviewed admissions with exacerbations of COPD, categorised by resuscitation status, to see if there were differences in prognostic features between groups. Methods: 53 acute admissions with exacerbations of COPD were reviewed between 1 December 2010 and 31 January. Groups were divided by resuscitation status: documented decision not to attempt resuscitation (DNR), no documented decision (NoD) and documented decision for resuscitation (ForR). Data were collected on individual prognostic factors; we then calculated prognostic indices against known criteria. P values were calculated using Mann–Whitney U test. Results: The significant findings were that patients in the DNR group had lower FEV1, more likely to have home oxygen and had a poorer functional status. Age, comorbidity, BMI and previous ITU admission were not found to be significantly different between the groups. When the prognostic indices were calculated the patients in the DNR group were found to have higher scores, correlating with poorer prognosis. Conclusions: From the results we can infer which factors are being used for resuscitation decisions in patients with COPD. Functional status and home oxygen are most relied upon with FEV1 somewhat less so. Age, comorbidity and BMI are not being taken into account, despite evidence to suggest they should be considered. We have also discovered that ADO and GSF are strong prognostic indicators for this cohort, although their application may not be appropriate (only two patients of the DNR group had a predicted 3-year mortality >50% on ADO index). This may reflect other factors (such as patient choice) that we have not evaluated. We feel that as many prognostic factors as available should be considered when making decisions on resuscitation as ultimately, this may also be the decision not to intubate.